Highlight Traditional Chinese Medicine nursing thinking and build "One Syndrome and One Product " ward (突出中医护理思维 建设"一证一品"病房) - WU Xinyuan (吴欣媛) (Journal of International Translational Medicine Limited, 2021)
The construction of " One Syndrome and One Product " specialized ward aims to highlight the characteristics and advantages of Traditional Chinese Medicine (TCM) nursing, promote innovation and development of TCM nursing techniques and improve the quality of nursing. This paper summarized the experience of construction of " One Syndrome and One Product " specialized ward, discussed its working mechanism and promoting effect on TCM nursing. Through the construction, the nursing staff's thinking and professional ability of TCM have been improved, and the patients have gained more experience of TCM and more professional nursing services. ("一证一品"专科模式病房建设项目旨在突出中医护理的特色和优势, 使中医护理在继承中创新发展, 更好地服务于人民。本文主要总结了"一证一品"模式病房建设过程中的相关经验, 包括工作机制以及对中医护理发展的推动作用, 通过模式病房的建设, 护理人员在中医思维和专科能力上得到了提升, 中医护理服务更显专业化。)